Inoculation of Pan02 cells produces tumor nodules in mouse pancreas: Characterization of a novel orthotopic pancreatic ductal adenocarcinoma tumor model for interventional studies. - James I Griffin; Xinyue Chen; Luqi Duan; Qingxin Mu; Rodney J Y Ho (PLoS ONE, 2024)
Preclinical models of cancer are vital for assessing and predicting efficacies and toxicities of novel treatments prior to testing in human subjects. Current pancreatic tumor models exhibit variable growth rates, unpredictable tumor size after implantation in non-native tissues, or require surgical implantation. Surgical implantation in the pancreas may produce not only unpredictable tumor uptake but could also elicit additional inflammatory responses. In searching for a pancreatic carcinoma cell that can be introduced into a mouse via simple injection, we found that Pan02, a murine ductal pancreatic adenocarcinoma derived from a pancreatic lesion of a C57BL/6 mouse, inoculated peritoneally can consistently produce pancreatic tumors. This intraperitoneal, but not intravenous, introduction of Pan02 cells leads to the attachment and growth of Pan02 in the pancreas before spreading to other tissues. Time-course tissue analysis indicates that the Pan02 cells first find, infiltrate, and grow within the pancreas, producing a pancreatic tumor model. This model appears to mimic pancreatic cancer development in humans and is the first reported use of Pan02 cells to produce orthotopic pancreatic and metastatic neoplasms in a mouse model without the need for tumor implantation within matrices or survival surgeries. This orthotopic pancreatic tumor model, with consistent tumor uptake, synchronized tumor development and survival, and predictable outcomes may enable and accelerate the preclinical evaluation of treatment candidates for pancreatic cancer.